Trajectory of service use among young Albertans with complex needs - Izakian, Hesam; Cui, Xinjie; Tough, Suzanne (International Journal of Population Data Science, 2018)
Introduction Youth with complex-needs are vulnerable as a consequence of exposure to social adversity and/or chronic health conditions, and are at a high risk of school failure and justice involvement. Information about the patterns of service use across government sectors that influence the life outcomes of complex-needs youth is unknown. Objectives and Approach Youth with complex needs often engage with multiple services across multiple government sectors for extended periods of time. Understanding the patterns and trajectory of their service use may inform programs, decision makers and government in the optimal allocation of resources to increase their life outcomes. It may reveal where and when interventions would be most effective to improve the life course for vulnerable youth. In this study, through a unique approach to link over 20 administrative longitudinal datasets and a novel trajectory clustering technique, the patterns of service use among complex-needs young Albertans is revealed and visualized. Results A trajectory clustering technique was applied to reveal patterns of service use among complex-needs individuals. Compared to the general population, higher proportions of youth with complex needs lived in low socio-economic neighborhoods, suffered from mental health issues, were high cost health service users, and had lower rates of high school completion. Furthermore, youth having complex needs for a longer period of time and who required multiple complex services in a given year had the poorest outcomes, in terms of high school completion, mental health issues, and other health problems. The majority of complex-needs youth came in contact with services via the education system, followed by child services/welfare. Conclusion/Implications The trajectories of service use among complex-needs youth reveals that these individuals are primarily identified through education. Consequently, educational supports would best address the development of effective programs including mental health supports and other needs.